Firehouse dog - Hutchings, Richard (U.S.A : Cartwheel books, 1993)
Lucky Hooper! He gets to live and work with real- life fire fighters. He watches them get ready to fight fires and helps them teach people about fire safety.
Keywords: Fire safety